The Unusual Reddish-Bloom Appearance in a Freshwater Fishpond at Kingolwira National Fish Farming Center, Morogoro, Tanzania - N. Kimambo, Offoro; R. Gumbo, Jabulani; A.M Msagati, Titus; Chikoore, Hector (International Journal of Environment, 2020)
The study aimed to examines a case of what constituted the uncommonly reddish-bloom appearance in the fishponds during the dry season (September 2018) at Kingolwira National Fish Farming Center located in Morogoro, Tanzania. The study used a benchtop FlowCAM® to investigate species' morphology. One-time assessment of physico-chemical characteristics during the event was performed from the reddish and non-reddish fishponds. Images were compared with the available literature, but also t-test statistics were performed to examine the difference between the fishponds. The results show that the fishponds were significantly (p